Clinical applications of curcumin (Curcuma longa) in oral disorders (Research, Society and Development, 2020)
Curcumin is an yellow pigment that is present in the rhizome of turmeric (Curcuma longa), a plant related to the ginger family (Zingiberaceae), originally from India. It is mainly used in cooking and aesthetics, but is also widespread in folk medicine, in the form of teas, gels and ointments. The aim of this study was to ascertain in the literature the clinical potential of curcumin in disorders in the bucomaxillofacial complex. For this, an integrative literature research published in the range from 2000 to 2020 was carried out in the online databases PubMed (National Libary of Medicine) and ScienceDirect. Using Descriptors and Synonyms MeSH, following 3 semantic fields: "Curcumin" in association with "Oral and Maxillofacial Pathology" and "Pharmacological Therapy".  From the 986 articles found, 20 were included in this article after the application of inclusion criteria, where significantly positive results were observed in treatments of pathologies such as leukoplakia, cystic adenoid carcinoma, lichen planus, submucosal fibrosis, oral mucositis and candidiasis. In addition, post-surgical complications such as pain, inflammatory edema and alveolar osteitis also had attenuated signs and symptoms due to the use of curcuminoids. In this sense, curcumin applies to dentistry as an anti-inflammatory, antifungal, antineoplastic and healing.